SPIDER WEB ATAU SHAJARAH AL-‘ILM?: Mencari Format Ideal Kajian Hadis Integratif di Indonesia - Benny Afwadzi (UIN Siber Syekh Nurjati Cirebon, 2019)
Spider Web and Shajarah al-lmIlm are two concepth of religious and scientific integration that are popular in the Islamic Religious College (PTKIN). The first concept is owned by UIN Sunan Kalijaga Yogyakarta, while the second concept is owned by UIN Maulana Malik Ibrahim Malang. Therefore, this article focuses on reviewing integrative traditions in both concepth of integration of religion and science. This article concludes that in Spider Web, hadith are in hadha>rah al-Nashsh which dialogue with hadha>rah al-‘ilm and are bridged by hadha>rah falsafah. In the concept there is also the word